2022
DOI: 10.1002/clc.23804
|View full text |Cite
|
Sign up to set email alerts
|

Association of early repolarization pattern and ventricular fibrillation in patients with vasospastic angina: A systematic review and meta‐analysis

Abstract: Background An early repolarization (ER) pattern is a risk factor for ventricular fibrillation (VF) in patients with vasospastic angina (VSA) caused by a coronary artery spasm. However, its detailed characteristics and prognostic value for VF remain unclear. Thus, we investigated the relationship between ER and VF in patients with VSA. Hypothesis The ER pattern is associated with VF in patients with VSA. Methods In this systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…483 A recent systematic review found that the risk of VF is approximately 5-fold higher in the presence of the ER pattern. 484 Conversely, in a report of 34 ER patients with a history of VF, 13 patients (38%) had VSA, and caution should be exercised with the combination of both diseases. 485 Furthermore, Brugada syndrome can be associated with VSA, and it has been reported that coronary spasm can induce VF by acting additively or synergistically on the arrhythmogenic component of Brugada syndrome.…”
Section: Mechanism Of Lethal Arrhythmias In Vsamentioning
confidence: 96%
“…483 A recent systematic review found that the risk of VF is approximately 5-fold higher in the presence of the ER pattern. 484 Conversely, in a report of 34 ER patients with a history of VF, 13 patients (38%) had VSA, and caution should be exercised with the combination of both diseases. 485 Furthermore, Brugada syndrome can be associated with VSA, and it has been reported that coronary spasm can induce VF by acting additively or synergistically on the arrhythmogenic component of Brugada syndrome.…”
Section: Mechanism Of Lethal Arrhythmias In Vsamentioning
confidence: 96%